Advances in Healthcare Technology Shaping the Future of Medical Care - Spekowius, Gerhard; Wendler, Thomas (Philips Research Book Series ;, 2006)
Improving healthcare and staying healthy is one of the most discussed and important issues in our society. Technology has played and will play an important role in many aspects of the healthcare system, and it offers new and better ways to solve the key health problems of the new century. This book describes valued contributions of technology for improving hospital and home healthcare, and gives a perspective on how they will influence critical aspects of future medical care. It provides an overview and discussion of trends, presents the state-of-the-art of important research areas, and highlights recent breakthrough results in selected fields, giving an outlook on game-changing developments in the coming decades. The material is arranged in 6 parts and a total of 31 chapters. The healthcare areas addressed are: General advances and trends in healthcare technology, diagnostic imaging, integration of imaging and therapy, molecular medicine, medical information technology and personal healthcare.